THE INFLUENCE OF SOCIAL MEDIA ON ENGLISH LANGUAGE USE - Davron Begmatov (Research Focus International Scientific Journal, 2025)
Social media has become a dominant force in shaping how people communicate, particularly in the English language. This article explores the profound influence of social media platforms on English language use, focusing on changes in vocabulary, grammar, and communication styles. It examines how platforms like Twitter, Instagram, and TikTok have introduced new linguistic trends, such as abbreviations, emojis, and hashtags, while also fostering global communication. The article concludes with implications for English language teaching and the need to adapt pedagogical approaches to address these evolving linguistic practices.